Expert Consensus for Thermal Ablation of Pulmonary Subsolid Nodules (2021 Edition) - Xin YE; Weijun FAN; Zhongmin WANG; Junjie WANG; Hui WANG; Jun WANG; Chuntang WANG; Lizhi NIU; Yong FANG; Shanzhi GU; Hui TIAN; Baodong LIU; et al. (Chinese Journal of Lung Cancer, 2021)
“The Expert Group on Tumor Ablation Therapy of Chinese Medical Doctor Association, The Tumor Ablation Committee of Chinese College of Interventionalists, The Society of Tumor Ablation Therapy of Chinese Anti-Cancer Association and The Ablation Expert Committee of the Chinese Society of Clinical Oncology” have organized multidisciplinary experts to formulate the consensus for thermal ablation of pulmonary subsolid nodules or ground-glass nodule (GGN). The expert consensus reviews current literatures and provides clinical practices for thermal ablation of GGN. The main contents include: (1) clinical evaluation of GGN, (2) procedures, indications, contraindications, outcomes evaluation and related complications of thermal ablation for GGN and (3) future development directions.